Analysis of Honey Bee Business Income, Tandung Billa Farmers Group, Palopo City - Fabiola B. Saroinsong; Yusfita Floria Rama; Hengki D. Walangitan (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to describe the management of honey bees and analyze the income of honey bees managed by farmer groups. The method used is observation and interviews. The cost-of-income analysis uses the assumptions: (1) honey bee business revenues during 2021, (2) calculated costs include maintenance, harvesting and packaging costs, (3) costs that have been incurred in the past (sunk costs) before 2021 are not taken into account. The results showed that honey production was not harvested every month and not all stup were harvested simultaneously because it depended on the availability of feed, during the spring it could be done up to 3 times/month while during the non-flowering season harvesting was only done once in 2 months. The number of stups per harvest is 3-4 stups, the amount of production per stup is 1-2 liters, the total production based on group production data is ± 205-210 liters/year. Furthermore, honey products are packaged in 2 different types of packaging, namely 80 ml packaging with a selling price of Rp. 25,000/bottle and 525 ml packaging with a selling price of Rp. 150,000/bottle, average sales in 2021 of 150-200 liters. Based on the results of the analysis, it was found that the production cost of Rp. 29,650,000/year with an income of Rp. 61,650,000/year, thus the net income of the farmer group in the farmer group is Rp. 32,000,000 with a benefit cost ratio of 1.1. Keywords: honey, income, community forestry Abstrak Penelitian bertujuan untuk mendeskripsikan pengelolaan lebah madu dan menganalisis pendapatan lebah madu yang dikelola kelompok tani. Metode yang digunakan adalah observasi dan wawancara. Analisis biaya pendapatan menggunakan asumsi: (1) penerimaan usaha lebah madu selama tahun 2021, (2) biaya yang diperhitungkan mencangkup biaya pemeliharaan, pemanenan dan pengemasan, (3) biaya yang sudah dikeluarkan pada masa lalu (sunk cost) sebelum tahun 2021 tidak diperhitungkan. hasil penelitian menunjukkan bahwa produksi madu tidak setiap bulan dipanen dan tidak semua stup dipanen bersamaan karena tergantung dari ketersediaan pakan, saat musim bunga bisa dilakukan sampai 3 kali/bulan sedangkan saat tidak musim bunga pemanenan hanya dilakukan 1 kali dalam 2 bulan. Jumlah stup per panen sebanyak 3-4 stup, jumlah produksi per stup 1-2 liter, total produksi berdasarkan data produksi kelompok sebesar ± 205-210 liter/tahun. Selanjutnya produk madu dikemas dalam 2 jenis kemasan yang berbeda yaitu kemasan 80 ml dengan harga jual Rp 25.000/botol dan kemasan 525 ml dengan harga jual Rp. 150.000/botol, rata-rata penjualan tahun 2021 sebanyak 150-200 liter. Berdasarkan hasil analisis diperoleh bahwa biaya produksi sebesar Rp. 29.650.000/tahun dengan penerimaan sebesar Rp. 61.650.000/tahun dengan demikian pendapatan bersih kelompok tani dalam kelompok tani sebesar yaitu sebesar Rp. 32.000.000 dengan benefit cost ratio 1,1. Kata Kunci: madu, pendapatan, hutan kemasyarakatan